2010
DOI: 10.1177/1049909110391646
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Program to Strengthen First Year Residents’ Proficiency in Leading End-of-Life Discussions

Abstract: A short, focused intervention can have significant impact on residents' communication skills in the setting of an end-of-life objective structured clinical examination (OSCE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Although Williams et al 22 showed improved overall performance of EOL conversations with standardized patients after an intensive workshop, several other interventions have not significantly improved overall performance despite similar amounts of teaching time. 12,13 The use of ''multiple day'' training programs (ranging from 24 to 105 hours) [23][24][25][26] or ''booster'' sessions 27,28 have been used successfully to improve the communication skills of more experienced clinicians.…”
Section: Szmuilowicz Et Almentioning
confidence: 97%
“…Although Williams et al 22 showed improved overall performance of EOL conversations with standardized patients after an intensive workshop, several other interventions have not significantly improved overall performance despite similar amounts of teaching time. 12,13 The use of ''multiple day'' training programs (ranging from 24 to 105 hours) [23][24][25][26] or ''booster'' sessions 27,28 have been used successfully to improve the communication skills of more experienced clinicians.…”
Section: Szmuilowicz Et Almentioning
confidence: 97%
“…17,18,23,24 However, it remains unclear as to which intervention or combination of interventions are superior for providing and sustaining this. Ahmed and colleagues 27 were able to show an improvement in residents' knowledge in palliative medicine with the establishment of a geriatric and palliative medicine division.…”
Section: Discussionmentioning
confidence: 98%
“…22 Educational interventions for residents have resulted in increased comfort and knowledge in providing palliative care. 17,18,23,24 However, it is unclear which intervention or combination of interventions are superior for providing and sustaining these results.…”
Section: Introductionmentioning
confidence: 96%
“…Klaristenfeld and colleagues 18 showed group discussion, role-playing, and instruction in advanced clinical decision making improved trainees' comfort with discussing EOL care with patient or families; 80% of participants felt they had been adequately trained for palliative care and valued it as an important training experience. Similarly, William and colleagues 22 showed a short but focused workshop on EOL significantly improved trainees' performance in a simulated encounter and clinical vignettes.…”
Section: Studies Categorized By Type Of Interventionsmentioning
confidence: 96%
“…These studies used a combination of methods, such as small group intervention/ discussions, [16][17][18]21,22,24 role-play, [16][17][18][19]21,23,24 ethics seminar, 20 lectures/instructions, 18,20,23 didactics coupled with role-play, 17 retreat for a day or two with presentations, discussions, role plays, 16,19,21 and unconventional/customized intervention like showing a movie to residents. 19 Alexander and colleagues 16 conducted a prospective study, which showed small group teaching with lectures, discussion, and role-play improved communication skills of residents.…”
Section: Studies Categorized By Type Of Interventionsmentioning
confidence: 99%